Total Hip Arthroplasty in an Inveterate Femoral Neck Fracture in a Patient with Congenital Insensitivity to Pain with Anhidrosis - Dagnino, Augusto; Ursino, Nicola; Ripamonti, Carlo A. M.; Fiorentini, Carlo E.; Scelsi, Michele; D'Ambrosi, Riccardo; Portinaro, Nicola M. (Joints, 2017)
Congenital insensitivity to pain with anhidrosis (CIPA) is an extremely rare disorder characterized by autonomic and sensory nerves malfunction with insensitivity to both deep and superficial painful stimuli, inability to sweat and produce tears, and mild to moderate mental retardation with self-mutilating behavior. Related consequences of inveterate musculoskeletal injuries represent a major issue for these patients, since pain cannot act as a protection mechanism. For the same reason, the patients are at risk during postoperative rehabilitation, which should be taken into account when selecting an orthopaedic implant. To our knowledge, only one case of total hip arthroplasty has been reported in the literature to date. A 21-year-old Caucasian male patient affected with CIPA arrived at our attention complaining about a functional limitation of the left hip. No history of trauma was reported. The X-rays showed an inveterate femoral neck fracture with a severe necrosis and resorption of the femoral head. We decided to perform a total hip arthroplasty with a cemented stem and a cemented dual mobility cup. The postoperative course and rehabilitation were satisfactory, with excellent clinical results, measured with the Harris Hip Score at 1 year.
Keywords: congenital insensitivity to pain with anhidrosis; total hip arthroplasty; femoral neck fracture; dual mobility cup; hereditary sensory autonomic neuropathy